2012
DOI: 10.1007/s12663-012-0355-9
|View full text |Cite
|
Sign up to set email alerts
|

Standards of Facial Esthetics: An Anthropometric Study

Abstract: Aim Anthropometry is an art and science used extensively for measuring the soft tissue proportions. While it is true that error is found in measurements of this kind, a great many trends of growth and development and therapy changes can be recorded with a significant degree of accuracy. Objective Facial proportion varies among the different ethnic groups and today, most of the available studies are done on western population. Hence an Anthropometric study was conducted in the local population. Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0
4

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 6 publications
6
29
0
4
Order By: Relevance
“…In horizontal to horizontal facial ratios on Indian American men, mouth face width index was consistent with previous studies done in Indian men [ 11 20 ] and Caucasian men [ 23 ]. The mandibular face width in Indian men [ 11 ] and intercanthal-nasal width in Caucasian men [ 22 ] indices were also similar to the present study whereas, mandibular-face width index in Caucasian men [ 23 ] and Indian men [ 20 ], intercanthal-nasal width in Indian men [ 11 20 ] and Caucasian men [ 23 ] studies showed statistically significant difference ( P <0.001). In the available literature search, I could not find the data on eye fissure intercanthal width, eye fissure nasal width, and eye fissure intercanthal mouth width indices for the comparison.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In horizontal to horizontal facial ratios on Indian American men, mouth face width index was consistent with previous studies done in Indian men [ 11 20 ] and Caucasian men [ 23 ]. The mandibular face width in Indian men [ 11 ] and intercanthal-nasal width in Caucasian men [ 22 ] indices were also similar to the present study whereas, mandibular-face width index in Caucasian men [ 23 ] and Indian men [ 20 ], intercanthal-nasal width in Indian men [ 11 20 ] and Caucasian men [ 23 ] studies showed statistically significant difference ( P <0.001). In the available literature search, I could not find the data on eye fissure intercanthal width, eye fissure nasal width, and eye fissure intercanthal mouth width indices for the comparison.…”
Section: Discussionsupporting
confidence: 91%
“…The upper lip-nose height index in Indian men [ 11 ], lower face-face height, nose-face height index, and upper lip-nose height index in Caucasian men [ 23 ], upper lip-nose height index and upper lip-mandible height in Indians [ 20 ], nose-face height index and upper lip-mandible height in Caucasian men [ 24 ] studies were also in agreement with present study whereas, lower face-face height and nose-face height index in Indian men [ 11 ], mandibulo-upper face height and upper lip-nose height index in Caucasian men [ 21 ], upper lip-nose height index and upper lip-mandible height in Caucasian men [ 22 ], upper face-face height and nose-lower face height in Caucasian men [ 24 ] studies showed statistically significant differences ( P <0.001). In the available literature search, I could not find the data on ear-lower face height and ear-nose height index for the comparison.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings shown in the above tables prove that the width of the bone framework in Indian Men is comparably smaller than their North American Causcasian counterparts and that the width of bone framework in Indian Female is also comparably smaller than their Causasian counterparts. [ 7 ] Indian faces tend to get fuller and tissues descend downwards and medially making it complicated for aesthetic correction. [ 8 9 10 ] Also in signifcant Indian population, the lower 1/3 rd of the face is much shorter in comparision to the upper 1/3 rd and the mid 1/3 rd of the face.…”
Section: Introductionmentioning
confidence: 99%